PRACTICALITY TEST: INTEGRATED AUGMENTED REALITY IN ENGLISH FOR CULINARY BOOK - Nurzahra Fathiyanabila Wicaksono; Levandra Balti; Anggita Pebrianti (Jurnal Muara Pendidikan, 2024)
This research aims to test the practicality of using Augmented Reality (AR) integrated in the book "English for Culinary" using descriptive quantitative methods. The research instrument, a practicality questionnaire, was distributed to lecturers and students of the Culinary Arts Education Study Program. The assessment is carried out based on four main indicators: usable, easy to use, appealing, and cost-effective. The results of the practicality test completed by the lecturer showed that the usable indicator obtained a score of 85, easy to use 80, appealing 86, and cost-effective 84, with an overall average score of 83.7, which is classified in the "very practical" category. Meanwhile, the results from students showed scores for usable indicators of 83, easy to use 81, appealing 85, and cost-effective 82, with an overall average of 83.7, which is in the "very practical" category. Based on these results, it can be concluded that the integration of AR in the book "English for Culinary" is very practical for both lecturers and students in the learning process.